2015
DOI: 10.1016/j.jbiotec.2015.06.389
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of nucleic acid aptamers targeting the capsid P domain of a human norovirus GII.4 strain

Abstract: Human noroviruses (NoV) are the leading cause of acute viral gastroenteritis worldwide. Significant antigenic diversity of NoV strains has limited the availability of broadly reactive ligands for design of detection assays. The purpose of this work was to produce and characterize single stranded (ss)DNA aptamers with binding specificity to human NoV using an easily produced NoV target-the P domain protein. Aptamer selection was done using SELEX (Systematic Evolution of Ligands by EXponential enrichment) direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 71 publications
6
41
0
Order By: Relevance
“…The docking simulation predictions were confirmed by mutational analysis of aptamer M6-2. Native M6-2 exhibited binding, considered a VLP/no-VLP ratio of >2.0 per convention (8, 19, 21), for all of the aptamer concentrations tested, except at 0.001 µM. None of the other mutated aptamers displayed binding at any concentration, confirming docking simulation predictions.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The docking simulation predictions were confirmed by mutational analysis of aptamer M6-2. Native M6-2 exhibited binding, considered a VLP/no-VLP ratio of >2.0 per convention (8, 19, 21), for all of the aptamer concentrations tested, except at 0.001 µM. None of the other mutated aptamers displayed binding at any concentration, confirming docking simulation predictions.…”
Section: Resultssupporting
confidence: 76%
“…A previously performed motif analysis was also used to identify a general interacting region of the ssDNA aptamer (Fig. 4A) (19). An earlier study reported docking between an ssDNA aptamer and the structure of the entire norovirus VP1 protein (22).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations